Behavioral and Memory Boosting Effects of Intellan and Cyanocobalamin in Mice - Najam, Rahela; Anser, Humera (Journal of Pharmacy and Nutrition Sciences, 2022)
The aim of this study was to compare the effect of selected drugs, Intellan and cyanocobalamin on some aspects of animal behavior, like effect on memory, depression, gross behavior and exploratory activity. Results of present investigations reveals cyanocobalamin to be a good memory enhancer and intellan also showed memory boosting effects in addition to anti-anxiety activity which affects overall performance.